Numerical simulation and experiments on mono-polar negative corona discharge applied in nanocomposites - Zhang, Jia-Wei; Song, Chen (IEEE transactions on dielectrics and electrical insulation, 2017)
The corona discharge techniques, which are employed to orient dipoles and built up charges inside functional polymers, can develop important commercial applications of electroactive polymers (EAPs) and electrets for energy storage devices, air filters, electroacoustic and electromechanical transducers. We propose hereby an elective hybrid approach to the point-plane corona modeling in order to obtain more accurate electron flow in unipolar corona discharge system. A coupled system of partial differential equations (PDEs) w.r.t. Navier-stokes equations and hydrodynamic drift diffusion equations described the nature of photo-ionization, where the secondary avalanche in the discharge process was demonstrated. The simulation was verified by comparison with Surface Potential (SP) measurement of the nano-composites after corona polarization. Consequently, the spacial electric potential distribution and initial surface potential could be obtained by the means of finite elements method (FEM), which provided a good numerical approach for the experimental data of electrostatic surface potential. In addition, the influence of nano particle on the charge retain ability of the insulating polymers was also investigated, which could be a guideline for designing an effective poling method on the functional polymers applied in electrical energy storage devices sensors, actuators and transducer etc.
Gesehen am 31.07.2018